Nutritional compositions, pathogenic microorganisms and heavy metal concentration in green turtle eggs (Chelonia mydas) from Terengganu and Sabah, Malaysia - Katni, Nor Hashikin; Azmi, Amirul Faiz Mohd; Abdullah, Maizah Mohd; Rusli, Mohd Uzair; Zakaria, Zunita; Azizan, Tengku Rinalfi Putra Tengku; Amat, Azlan Che’; Saad, Mohd Zamri; Yasin, Ina Salwany Md.; Nazarudin, Muhammad Farhan; Hassim, Hasliza Abu (Frontiers in Marine Science, 2022)
A total of 60 green turtle eggs were obtained from sampling sites in Terengganu and Sabah, Malaysia. Isolation and identification of bacteria from these eggs resulted in 12 genera of Gram-negative bacteria with 12 different species. The most frequently isolated bacteria were Salmonella (30.9%) and Proteus (23.7%). The rest of the microorganisms were Aeromonas, Escherichia, Citrobacter, Enterobacter, Klebsiella, Morganella, Pseudomonas, Shigella, Serratia and Photobacterium. A slight difference in total crude protein content was recorded in the samples from Terengganu and Sabah, at 16.3% Dry matter (DM) and 15.8% DM, respectively. Meanwhile, the crude fat content found in the samples from Terengganu was 9.88% DM and 7.79% DM from Sabah. In this study, α-linolenic acid, C18:3 n-3 (Terengganu: 16.87% DM) and linoleic acid, C18:2 n-6 (Sabah: 15.19% DM) were the most prevalent fatty acids in both samples. The green turtle egg samples from Terengganu showed higher value of total saturated fatty acid, total C18:3 n-3 and C18:2 n-6 and total polyunsaturated fatty acids as compared to green turtle eggs from Sabah. The results also revealed that majority of the essential amino acids (EAA) recorded in samples from both sampling sites was lysine (9.67% DM), with higher value recorded in green turtle egg from Terengganu. However, there were no significant differences (p>0.05) in the nutritional compositions, fatty acid contents and amino acid compositions of the samples between the two sampling sites. Meanwhile, statistical analysis showed significant differences in heavy metal concentrations between the two sampling sites for all the six heavy metals detected in this study (Hg, Cd, Pb, Mn, Zn and Cu). The ranking of heavy metals concentration in turtle eggs from both sampling sites, in decreasing order is as follows: Zn > Cu > Mn > Pb > Cd > Hg. Overall, these results reveal the contents and contaminations of a green turtle egg, which may raise concern on public health risks. Findings from this study will also be beneficial for the future conservation of green turtle population when the consumption of their eggs should be stopped.